Respuesta :
we can use point-slope form (since we have the slope, and 1 ordered pair)
point-slope form is y-y1=m(x-x1)
x=-5
y=4
m=3
y-(4)=3(x-(-5)
point-slope form is y-y1=m(x-x1)
x=-5
y=4
m=3
y-(4)=3(x-(-5)
our point-slope formula is [tex](y- y_{1} )=m(x-x_{1})[/tex]
m=slope
[tex] x_{1} = -5[/tex]
[tex] y_{1} =4[/tex]
Therefor, when we input our values and simplify, we get...
[tex](y-(4))=3(x-(-5) \\ y-4=3x+15 \\ y=3x+19[/tex]
m=slope
[tex] x_{1} = -5[/tex]
[tex] y_{1} =4[/tex]
Therefor, when we input our values and simplify, we get...
[tex](y-(4))=3(x-(-5) \\ y-4=3x+15 \\ y=3x+19[/tex]